A novel comprehensive evaluation method for the corrosion initiation life of RC hollow piles in chloride environments. (20th July 2020) - Shao, Wei; Nie, Yinghui; Liang, Fayun; Shi, Danda
Highlights: A modified diffusion model of chloride ions in RC hollow piles is proposed. A comprehensive method is proposed for evaluating the corrosion initiation life. A sensitivity analysis on the main influencing parameters is conducted. The comparative analysis of three different prediction methods is performed. Abstract: A modified diffusion model of chloride ions in reinforced concrete (RC) hollow piles is proposed by taking into account the ageing of the pile concrete, loading level, environmental temperature and relative humidity. The corrosion initiation life of RC hollow piles is predicted by deterministic and probabilistic methods. In addition, by combining deterministic and probabilistic methods, a novel comprehensive method is proposed for evaluating the corrosion initiation life of RC hollow piles in chloride environments. A sensitivity analysis on the main influencing parameters is conducted for the prediction of the corrosion initiation life by the comprehensive method. Finally, the comparative analysis of three different prediction methods is also performed. The results show that the corrosion initiation life calculated by the comprehensive method decreases with increasing environmental temperature, relative humidity, water-cement ratio and initial surface chloride concentration, while it increases with increasing concrete cover depth and chloride threshold level. The comprehensive method is more reasonable than the deterministic and probabilistic methods for predicting the corrosion initiation life of RC hollow piles in chloride environments.